OPTIMALISASI PROBLEM BASED LEARNING PADA MATA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Aulina Prayoga Ardhana; Ike Yuli Mustika Dewi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Optimizing Problem Based Learning (PBL) in mathematics learning in elementary schools. This research is based on the low interest in learning mathematics among students, which is caused by difficulty understanding concepts and lack of motivation. Monotonous learning methods, such as lectures, exacerbate this situation, resulting in passive students and less than optimal learning outcomes. PBL, as a problem-centered learning approach, is believed to be able to overcome these problems. The problem formulation is related to the concept, characteristics, planning, and supporting and inhibiting factors of the PBL model. The research method used is Systematic Review, which allows researchers to systematically identify, assess, and interpret all relevant studies to answer research questions. PBL is a learning model that actively involves students in the learning process through solving real problems. Effective PBL has characteristics, such as relevant and interesting problems, focus on the problem solving process, effective teacher guidance, comprehensive evaluation, and integration with other learning methods. Collaborative PBL planning between teachers and students, as well as systematic implementation, is the key to the success of PBL. PBL, with proper planning and implementation, has the potential to increase students' understanding of mathematical concepts, develop critical thinking and problem solving skills, and increase students' learning motivation in elementary schools.